2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037154
|View full text |Cite
|
Sign up to set email alerts
|

Subject-specific shoulder muscle attachment region prediction using statistical shape models: A validity study

Abstract: Subject-specific musculoskeletal models can predict accurate joint and muscle biomechanics thereby helping clinicians and surgeons. Current modeling strategies do not incorporate accurate subject-specific muscle parameters. This study reports a statistical shape model (SSM) based method to predict subject-specific muscle attachment regions on shoulder bones and illustrates the concurrent validity of the predictions. Augmented SSMs of scapula and humerus bones were built using bone meshes and five muscle attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Because the scapular SSM and fitting method showed good accuracy for the prediction of landmarks and measurements in previous studies, 25,26 we did not re-evaluate this ability for the current muscle attachment points. Moreover, as demonstrated by Salhi et al, 29 the muscle attachment points on the scapula are expected to be indicated with higher accuracy than the muscle attachment points on the humerus because of the more distinct anatomic regions of the scapula. Third, we defined the muscle attachment points instead of using the complete muscle attachment regions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Because the scapular SSM and fitting method showed good accuracy for the prediction of landmarks and measurements in previous studies, 25,26 we did not re-evaluate this ability for the current muscle attachment points. Moreover, as demonstrated by Salhi et al, 29 the muscle attachment points on the scapula are expected to be indicated with higher accuracy than the muscle attachment points on the humerus because of the more distinct anatomic regions of the scapula. Third, we defined the muscle attachment points instead of using the complete muscle attachment regions.…”
Section: Discussionmentioning
confidence: 95%
“…17,24 Our results are comparable to those of other SSM-based landmark identification methods described in the literature. Salhi et al 29 investigated the prediction accuracy of subjectspecific muscle attachment regions using a healthy scapular and humeral SSM. For the humerus, they reported an average RMS error between 0.4 and 1.7 mm and a Hausdorff distance between 1.6 and 4.8 mm for all muscle attachment regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For clinical use, the key property of the SSM lies in the dense correspondence established during the registration process, which identifies the points sharing the same anatomical characteristics [2], [16], [17]. This feature has been effectively used to embed bony SSM with landmark-based anatomical information such as muscle insertions [18] or identify cortical bone thickness [13]. Moreover, the generative capabilities of these models enable the exploration of the shape coefficient representation within the valid anatomical shape variation [2], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Statistical shape models (SSMs) provide a valuable way to describe shape variability within a training dataset. Since their introduction (Cootes and Taylor 2001), these models have been used for multiple applications: to automatically segment bone structures (Lamecker et al 2004;Ma et al 2017), to study the shapes of human anatomy (Sarkalkan et al 2014;Salhi et al 2017;Sintini et al 2018;Casier et al 2018), to virtually reconstruct large bone defects (Vanden Berghe et al 2017;Poltaretskyi et al 2017;Plessers et al 2018;Abler et al 2018), to build 3D models starting from 2D information (Grassi et al 2017;Mutsvangwa et al 2017). The main concept behind SSM techniques is to perform principal component analysis (PCA) on corresponding landmarks derived from the dataset objects and to extract the main modes of variation.…”
Section: Introductionmentioning
confidence: 99%